Effect of Potassium Sulfate (K2SO4) and Chicken Manure Application on Productivity, Morphology, Physiology, and Antioxidant Activity of Shallots in Floating Cultivation - chindy charin marlisa; Susilawati Susilawati; Irmawati Irmawati (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2026)
Shallot is one of the vegetable commodities that has long been intensively cultivated by farmers. In addition, shallots are also a short-lived and commercial vegetable commodity. This study aims to evaluate the application of chicken manure and potassium sulfate (K2SO4) fertilizer on the growth and yield of shallot plants (Allium ascalonicum L.) cultivated in a floating manner. This research was conducted in Terawas Village, STL ULU Terawas District, South Sumatra. From May to July 2024. This research method Factorial Randomize Block Design (RAKF), consisting of 2 factors, namely the first factor of chicken manure consisting of 4 levels, and the second factor is sulfur fertilizer from K2SO4 consisting of 4 levels. With 3 block, in each block it was 3 planted plants. 3 treatment groups and 3 replications each replication consists of 16 plant units, resulting in a total of 144 plants used in this study. This treatment is the first factor: P0 = control (without chicken manure), P1 = 1 kg/polybag chicken manure, P2 = 2 kg/polybag chicken manure, P3 = 3 kg/polybag chicken manure. Second factor: S0 = control (without potassium sulfate fertilizer (K2SO4), S1 = potassium sulfate fertilizer (K2SO4) 100 kg/ha, S2 = potassium sulfate fertilizer (K2SO4) 200 kg/ha, S3 = potassium sulfate fertilizer (K2SO4) 300 kg/ha. Parameters observed included plant height, number of leaves, number of tillers, wet stover weight, tuber diameter, fresh tuber weight, wind-dried tuber weight, root length, tuber length, tuber number, tuber volume, hectare-1 production, chlorophyll analysis and flavonoid content. Dosing potassium sulfate fertilizer (K2SO4) with an optimal dose of 142.5 kg/ha on the variable of estimated production per/ha, 174 kg/ha on the variable of tuber weight, 210 kg/ha on the variable of tuber volume, 154 kg/ha on the variable of wind dry weight, 214.45 kg/ha on the variable of antioxidant activity (flavonoids).